In the shadow of fear : America and the world in 1950 - Bunker, Nick (Basic Books, Hachette Book Group, 2023)
"Halfway through the twentieth century, the United States towered over the world in industrial might. After winning the 1948 election, Harry Truman hoped to use this economic strength to build on FDR's achievements with new liberal reforms. But then, in just ten months between September 1949 and June 1950, the president's ambitions were overtaken by events that left the country gripped by rage and fear. The Soviets tested an atomic bomb, Mao's army swept through China, and at home Truman faced labor unrest and a Republican Party desperate for power. In the Shadow of Fear is an innovative and gripping history of this pivotal moment. Recounting the launch of Senator Joe McCarthy's anti-communist crusade, the defeat of Truman's liberal program, and the start of the Korean War, prizewinning historian Nick Bunker shows us a polarized nation facing crises at home and abroad--a story with deep resonances today"--